2014
DOI: 10.1159/000360928
|View full text |Cite
|
Sign up to set email alerts
|

Should a Drain Be Placed in Early Breast Cancer Surgery?

Abstract: Background: The current surgical debate has led to a reduction in the extent of surgery performed and thereby to a reduced occurrence of surgical trauma and, over the recent years, reduced seroma formation. This reduction in surgical procedures calls the need for a drain into question. Method: Using Google Scholar and the National Library of Medicine (PubMed), a literature review was performed on systematic reviews and meta-analyses regarding breast cancer surgery ± axillary dissection. Additionally, randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
7
1
Order By: Relevance
“…Previous research into the effectiveness of prophylactic drainage in reducing the incidence of complications following gastrointestinal, 25 vascular, 26 thyroid, 27 and breast cancer surgery 28,29 have not universally substantiated a benefit to drainage. Additionally, the presence of a prophylactic drain remaining in a postoperative wound may increase the risk of infection of the surgical site and be a cause of postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into the effectiveness of prophylactic drainage in reducing the incidence of complications following gastrointestinal, 25 vascular, 26 thyroid, 27 and breast cancer surgery 28,29 have not universally substantiated a benefit to drainage. Additionally, the presence of a prophylactic drain remaining in a postoperative wound may increase the risk of infection of the surgical site and be a cause of postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…Among breast cancer patients undergoing surgery, this rate can be as high as 90% 16 , 17 . However, over recent years, the possibility of not draining the axilla has been studied 11 , 12 since seroma formation rates tend to remain very high even with the use of drains 18 . This complication occurs secondary to the disruption of lymph channels, an inevitable consequence of extensive surgical dissection and disruption of tissue planes, creating a dead space 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Axillary drainage has become a subject of debate in recent years since it tends to prolong hospitalization times 11 and creates discomfort, exerting a negative psychological impact on patients who have undergone this treatment 5 , 12 , 13 . Drainage is also associated with limitations to activities of daily living that may include difficulty in dressing and problems with sleeping 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data showed that the use of drains was associated with a prolonged hospitalization in 50% of BC. This finding is consistent with an analysis of five systematic reviews which concluded that the insertion of a drain is associated with a longer hospital stay and reduced seroma formation …”
mentioning
confidence: 99%